N-Nonacosadienes from the marine haptophytes Emiliania huxleyi and Gephyrocapsa oceanica. (March 2015) - Nakamura, Hideto; Sawada, Ken; Araie, Hiroya; Suzuki, Iwane; Shiraiwa, Yoshihiro
Graphical abstract: Cultured Emiliania huxleyi NIES837 and Gephyrocapsa oceanica NIES1315 abundantly produce C29 alkenes, including 2, 20-nonacosadiene and 3, 20-nonacosadiene identified. Highlights: E. huxleyi NIES837 and G. oceanica NIES1315 produces abundantly nonacosadienes. Double bond positions in C29 alkenes were determined by MS of their DMDS adducts. The most abundant C29 alkene isomer was determined as 2, 20-nonacosadiene. Nonacosadienes have potential for being distinct haptophyte biomarkers. Abstract: The hydrocarbons in cultures of marine haptophytes Emiliania huxleyi NIES837 and Gephyrocapsa oceanica NIES1315 were analyzed, and nonacosadienes and hentriacontadienes were detected as the major compounds in both strains. C29 and C31 monoenes and di-, tri- and tetra-unsaturated C33 alkenes were also detected as minor compounds but not C37 and C38 alkenes. The positions of the double bonds in the C29 and C31 alkenes were determined by mass spectrometry of their dimethyl disulfide (DMDS) adducts. Among the four C29 alkenes identified, the most abundant isomer was 2, 20-nonacosadiene, and the other three compounds were 1, 20-nonacosadiene, 3, 20-nonacosadiene and 9-nonacosene, respectively. Hitherto, 2, 20-nonacosadiene and 3, 20-nonacosadiene were unknown to be natural products. The double bond at the n -9 (ω9) position in these C29 alkenes is hypothesized to be derived from precursors of unsaturated fatty acids possessing an n -9 double bond, such as (9Z)-9-octadecenoic acid. Nonacosadienes have the potential for being used as distinct haptophyte biomarkers.